Structure and morphology of spinel MgFe2O4 nanoparticles for water purification - Demeuova, Gulzat; Mauit, Ozhet; Ualibek, Oral; Toktarbaiuly, Olzat; Baisaryev, Murat; Sugurbekova, Gulnar; Kurbanova, Aliya (The 6th International Conference on Nanomaterials and Advanced Energy Storage Systems. Institute of Batteries LLP, Nazarbayev University, and PI “National Laboratory Astana”., 2018)
In this work, spinel magnesium ferrite MgFe2O4 nanoparticles were synthesized by convential sol-gel methods. The study was focused on obtaining nanoparticles with the maximum content of specified ferrites, nanosized and uniform particles, with high crystallinity for water purification application....
Keywords: water purification